Marriage Dispensation due to Extramarital Pregnancy: The Study on the Decision by the Religious Court of South Jakarta (2010-2011) - Isnawati Rais (Universitas Islam Negeri Jakarta, 2018)
The Marriage law in Indonesia sets the marriageable age at which a person is allowed to marry is 19 (nineteen) years old for men and 16 (sixteen) years old for women. This study focuses on legal decisions and judges’ consideration in establishing the application for marriage dispensation at the Religious Court of South Jakarta due to extramarital pregnancy. This study shows that the Court decision to grant the application for marriage dispensation at the Religious Court due to extramarital pregnancy is primarily based on the argument to avoid harmfulness. Using case study research, three court decisions stipulated by the Religious Court Decision Number: 056/Pdt.P/2010/PA.JS, Decision Number: 219/Pdt.P/2011/PA.JS and Decision Number: 197/Pdt.P/2011/PA granting the application for marriage dispensation due to extramarital pregnancy were analysed. The legal consideration formulated by the Panel of Judges is to avoid harm and is not contrary to the legislation. This means the judge’s consideration in determining the marriage dispensation due to extramarital pregnancy is not only based on the provisions stated in Article 7 paragraph (2) of the Law No. 1/1974 concerning Marriage jo. Article 15 paragraph (2) of the Compilation of the Islamic Law, but also on the consideration made by the Panel of Judges as the harms might occur if the application for marriage dispensation is refused. In determining this consideration of harms, it appears that they are influenced by their religious views and the social consequences.